Fractionation of bambangan kernel fat by two-stage fractionation and ther characteristics - Norazlina Mohammad Ridwan (2020)
Given the demand for new fats and oils and the limited research on bambangan kernel fat (BKF), this study aimed to fractionate BKF by two-stage acetone fractionation and to determine its physicochemical properties such as fatty acids by gas chromatography (GC), triglycerides (TAGs) by high-performance liquid chromatography (HPLC), iodine value (IV), acid value (AV), Free fatty acid (FFA), peroxide value (PV), slip melting point (SMP) and solid fat content (SFC) by pulse nuclear magnetic resonance (pNMR). The thermal (melting and crystallization) and polymorphic behaviors, as well as the morphological structures, were also determined using differential scanning calorimetry (DSC), X-Ray Diffraction (XRD), and polarized light microscopy (PLM). The major fatty acids of all stearin fractions were palmitic, stearic, and oleic acids, with the first stearin (Fraction-I) having a higher stearic acid (48.50%) but lower oleic acid (33.76%) content than the second stearin (Fraction-III). High SMP (36.3°C) and low IV, PV and AV (39.9 g iodine/100 g, 1.03 mEq/g and 0.93 mgKOH/g respectively) values were found in Fraction-III compared to Fraction-I. The SFC did not drop to 0% at body temperature, which was shifted to 0% above 40°C for both stearin fractions, which indicated it is heat-resistant. FI and FIII that composed of symmetrical SOS of 55.83% and 64.70% respectively are the valuable heat-resistance cocoa butter improver (CBI) fat produced from the fractionated BKF. The melting curve of the stearin fractions showed a similar single curve with cocoa butter (CB) but shifted towards the right. Both the stearin fractions melted and crystallized rapidly at high temperatures with one maximum peaks starting at 20.30−21.74°C and ending at 38.72−42.45°C (melting), and 17.05−18.46°C and ended at 5.63−8.20°C (crystallization). The melting curve for the stearin tended to be sharper and showed higher melting properties than pure BKF and CB. They exhibited β polymorphic form, which was similar to that of CB. Moreover, the stearin fractions showed spherulites microstructure consists of needle-like crystals radiating from central nuclei. This study shows that the BKF fractions (stearins) could be used as suitable raw materials for developing new fatty products in the food industry, especially the confectionery industries.